Pengaruh Perbedaan Penggunaan Bahan Penghancur Pati Pisang Kepok (Musa paradisiaca var ABB) Pregelatinasi dan Explotab terhadap Sifat Fisik dan Disolusi Tablet Parasetamol - Laksmita, Meirisa Mona; , Gunawan Setiyadi, M.Sc., Apt (2017)
The disintegrant is one of excipients used in the nufacture of tablets. Kepok banana starch's can be used as a integrant but flow abilityand compressibility are poor, so it needs to be modified pregelatinization. Pregelatinized starch is made by heating to 60℃. Explotab is a disintegrant that commonly used in the manufacture of tablets. This study was conducted to determine the effect of different types of disintegrant of pregelatinized kepok banana starch (Musa paradisiaca var ABB) and Explotab on physical properties and dissolution of paracetamol tablets. Tablets were made with pregelatinized kepok banana starch or Explotab as the disintegrant four formulas for each. The concentrations of the disintegrant were F1 (2%), F2 (4%), F3 (6%) and F4 (8%). Test were performed for each formula such as quality tests of granules physical properties, quality test of tablets physical properties and tablets dissolution. The test results were analyzed using two-way Anova and continued with LSD-t test when there were significant differences. The results obtained from the study showed that the difference of disintegrant affect tablets friability and disintegration time. The difference of concentration disintegrant affect tablets disintegration time. The results of dissolution test of paracetamol tablets showed that F3 and F4 of gelatinized kepok banana starch can dissolve paracetamol > 80% within 30 minutes but Explotab only dissolves paracetamol < 80% within 30 minutes. The value DE60pregelatinized kepok banana starch is better than Explotab.